Biosorption of transition metals by freely suspended and Ca-alginate immobilised with Chlorella vulgaris: Kinetic and equilibrium modeling - Ahmad, A. (Elsevier Ltd, 2018)
In this study, biosorption of Fe (II), Mn (II), and Zn (II) ions, from aqueous solution with free (non-immobilised) and Ca-alginate beads with immobilised Chlorella vulgaris biomass was investigated. Effects of pH, metal ions concentration, biosorbent dosages and contact time on the biosorption of selected metallic ions were studied. The maximum biosorption of Fe (II) 129.83, Mn (II) 115.90 and Zn (II) 105.29 mg/g was achieved with Ca-alginate immobilised microalgal biomass at optimum pH of 6.0, biomass dosage, 0.4 g/L, and contact time of 300 min and at 25 Â°C temperature. The biosorption efficiency of freely suspended and immobilised C. vulgaris biomass for the heavy metals removal from the industrial wastewater Palm Oil Mill Effluent (POME) was validated. The metallic ions biosorption on the Ca-alginate immobilised microalgae followed the pseudo-second-order kinetics model and the experimental data were well fitted to the Langmuir and D-R isotherm models. The calculated thermodynamic parameters, ÎGo, ÎHo and ÎSo exhibited that the biosorption of all tested metal ions onto freely suspended and Ca-alginate immobilised algal cells was feasible, spontaneous and exothermic in nature under observed conditions. The biosorption mechanism of C. vulgaris illustrated by FTIR and XPS showed bands conforming to CsbndN, sbndOH, COOsbnd, sbndCH, CdbndC, CdbndS and sbndCsbnd groups are closely related with the binding of heavy metals. The SEM showed porous morphology which greatly helps in the biosorption of heavy metals. This study confirmed that immobilisation of C. vulgaris in alginate beads constitute a favorable, effective, economical and biodegradable biosorbent material for the removal of heavy metals pollution in the environment. Â© 2017 Elsevier Ltd